Assessing the impact of novel risk loci on Alzheimer’s and Parkinson’s diseases in a Chinese Han cohort - Yan, Huimin; Liu, Minglei; Gao, Yuan; Yuan, Yanpeng; Liu, Xiaojing; Wang, Yangyang; Li, Lanjun; Wang, Qingzhi; Wang, Yanlin; Shi, Changhe; Xu, Yuming; Yang, Jing (Frontiers in Neurology, 2024)
Genetic factors contribute significantly to the variation in Alzheimer's disease (AD) risk among individuals, and these factors exhibit variation across different racial groups. A recent extensive genome-wide association study of European origin identified seven novel risk loci associated with late-onset AD (LOAD) in Caucasians. However, it remains unclear whether these newly identified loci are associated with AD in Asian populations. As both Alzheimer's disease (AD) and Parkinson's disease (PD) are neurodegenerative conditions with some shared pathological processes, this study aimed to investigate the potential of these newly identified loci as risk factors for both AD and PD. A case-control study was conducted, involving 211 AD patients, 508 PD patients (including 117 with dementia), and 412 healthy individuals. Age and sex stratification analysis revealed that rs871269/TNIP1 was associated with LOAD (p = 0.035), and rs5011436/TMEM106B was associated with AD in males (p = 0.044) in the genotype model. In the allele model, rs871269/TNIP1 was found to be associated with PD in the Chinese Han population (p = 0.0035, OR 0.741, 95% CI 0.559-0.983), and rs708382/GRN was identified as a risk factor for Parkinson's disease dementia (PDD) in the Chinese Han population (p = 0.004, odds ratio (OR) 0.354, 95% confidence interval (CI) 0.171-0.733). However, no significant associations with AD or PD were observed for the remaining four loci (rs113020870/AGRN, rs6891966/HAVCR2, rs2452170/NTN5, rs1761461/LILRB2) in terms of allele or genotype frequencies. This study identifies rs871269/TNIP1 as a potential risk factor for both AD and PD, rs708382/GRN as a risk factor for PDD, and rs5011436/TMEM106B as associated with AD in males when stratified by age.